Depression and Associated Factors Among Tea Garden Workers of Selected Tea Garden in Sylhet (Journal of Preventive and Social Medicine, 2021)
Background: Tea garden workers play a crucial role to the economy of the country. Majority of the tea garden worker are females and suffer from various health problems including depression. The study was conducted to assess the extent of depression among the tea garden workers and their associated factors.Methods: This descriptive type of cross-sectional study was conducted among 192 respondents in a selected tea garden name Jaflong tea garden in Goainghat, Sylhet. An interview was conducted face to face with the respondents for data collection with a semi-structured questionnaire. To assess the depression, the respondents were at first screened by General Health Questionnaire 12 and then who scored more than 2 were clinically assessed by Diagnostic and statistical manual fourth edition(DSM-4). After then Hamilton Rating scale for depression (HRDS) was used to measure the severity of depression among the diagnosed depressed cases. The study was conducted at Jaflong tea garden in Goainghat, Sylhet. The study period extended from September 2015 to February 2016.Results: The results show about two third of the respondents were distributed in the age group 30-40 years. Out of the total 192 respondents 72 were male (37%) and 120 were female (63%).About four-fifth (80%) of the respondents were illiterate compared to only 20% respondents who had primary level education and all the respondents were inhabitant of slum. The monthly family income of the respondents was from 900 taka to 2500 taka. Among the total 192 respondents, 78 (40.7%) had a working experience of 16-21 years followed by 62 (32.3%) had 10-15 years and 52 (27%) had 4-9 years. Almost 80% of the respondents (n=152) worked for 8 hours. The proportion of depression among the particular tea garden workers were 21%. Altogether 40 respondents (out of 192) were found as patient of depression and the prevalence rate is more in ever married women of less than or equal to 35 years old and whose experience is 16-21 years and have to work more than or equal to 8 hours.Conclusion: Workers with a potential to suffer from depression may be a crucial economic problem for employers. So from the present study, it is highlighted that mental illness is a significant public health problem in particular occupational sector that need to be addressed to the concerned people.JOPSOM 2020; 39(2): 14-19